超连通图的充分条件 - 郭利涛 (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2018)
Let G be a connected graph. The connectivity κ(G) of a connected graph G is the least positive integer k such that there is F⊂V, | F | = k, and G—F is disconnected or is a trivial graph. If every minimum vertex cut isolates a vertex of G, a graph G is super connected or super-κ. Define the inverse degree of a graph G with no isolated vertices as . In this paper,we show that let G be a connected graph with order n and minimum degree δ, if , then G is super-κ.